The Impact of Growth-Promoting Bacteria and Residual Phosphorus Rates on the Nutritional Efficiency and Production of Ratoon Sugarcane - Fernandes, Guilherme Carlos [UNESP]; Rosa, Poliana Aparecida Leonel [UNESP]; Galindo, Fernando Shintate [UNESP]; da Silva Oliveira, Carlos Eduardo; Korany, Shereen Magdy; Sonbol, Hana; Alsherif, Emad Ali; Hamed, Seham M.; Ito, William Cesar Nishimoto [UNESP]; Torrezan, Gabrielly Freire [UNESP]; Sobrinho, Renato Lustosa [UNESP]; Schussler, Caio Henrique Oliveira [UNESP]; et al. (Springer Nature, 2025)
Phosphorus deficiency limits sugarcane productivity in tropical and weathered soils, where traditional fertilization is inefficient due to phosphorus fixation by iron and aluminum oxides. Sustainable management is crucial for ratoon sugarcane, which dominates crops in tropical savannas. This study investigates the combined use of residual phosphorus fertilization and plant growth promoting bacteria (PGPB), Azospirillum brasilense, Bacillus subtilis, and Pseudomonas fluorescens, to increase nutrient availability, root development, and reduce dependence on chemical inputs. PGPB inoculation increased nutrient accumulation in straw and stalks, and consequently increased stalk productivity in second ratoon sugarcane. Co-inoculation with Azospirillum brasilense and Pseudomonas fluorescens, increased phosphorus accumulation by up to 764% and 768% compared to controls in straw and stalks, respectively. The treatments also increased the accumulation of macronutrients in sugarcane. The highest productivity was associated with inoculation of Azospirillum brasilense with Pseudomonas fluorescens at a residual dose of 135 kg ha−1, with an increase of 42% compared to the control. The inoculated plants consistently outperformed non-inoculated controls at all residual P doses. In addition, inoculation improved the uptake of calcium, magnesium, sulfur, boron, iron, manganese, copper and zinc, varying with the bacterial combinations and P levels. Inoculation with PGPB significantly improved nutrient uptake and stalk productivity under conditions of low residual phosphorus. Co-inoculation with A. brasilense and P. fluorescens was most effective, particularly at a dose of 135 kg ha−1 P2O5. Inoculated treatments outperformed controls even at lower P doses, highlighting the potential of combining microbial inoculants with residual fertilization to sustain sugarcane productivity while reducing fertilizer dependence in tropical savanna soils.